The Role of SDG 4: Quality Education on the Internationalization of Indonesia's Education - Mochammad Nirzam Putra Ramadhan (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2023)
This research explores the role and the effect of SDG 4: Quality Education in Indonesia's effort to internationalize its education system. This qualitative research utilizes the library research method to analyze the effect and role that SDG 4 has regarding the internationalization of Indonesia's education system. Through this research, it is found that SDG 4 plays a significant role in Indonesia's decision-making regarding the internationalization of its education, and SDG 4 became the base framework for the program that Indonesia designed and executed. SDG 4 plays a significant role in Indonesia's education system internationalization through its policies, budget allocations, and the implementation of SDG 4's targets and indicators in Indonesia's education internationalization programs.